INVESTIGATE THE FACTORS THAT INFLUENCE FOREIGN TOURISTS' DECISION TO VISIT GARUDA WISNU KENCANA - Fuadi Afif; Rachmadi, Hari (Family Welfare Education, 2023)
The goal of this study was to examine the variables that affect foreign tourists' decisions to visit the Garuda Wisnu Kencana Cultural Park. The purpose of this study is to answer the following research questions: